GROWTH RESPONSE AND As ACCUMULATION IN TISSUE IN CHICKENS FED ARSANILIC ACID - ΔΕΜΕΡΤΖΗΣ Π. Ν. (Journal of the Hellenic Veterinary Medical Society, 1972)
Experiments were carried out to determine the effect of arsanilic acid on chickens. Growth response for chickens fed arsanilic acid and kept in cages was very consistent in comparison with their respective control group. The level of arsenic retention in tissue was found to be similar to that found by other workers for chickens fed arsanilic acid in cages. Chickens fed arsanilic acid and kept in deep litter showed a higher accumulation of arsenic in tissue. Arsenic in the litter was found to increase with time though this increase was not linear.